ANALYSIS OF THE COMPARISON OF INDIGENOUS FARMERS AND NON- INDIGENOUS RICE FARMERS INCOME (ORIZA SATIVA) AT THE VILLAGE KESIO LALOLAE DISTRICT OF KOLAKA - Muhtar Amin (Agribusiness Journal, 2016)
Analysis of comparison of indigenous farmers and non-indigenous rice farmers income on paddy rice farming at the village Kesio Lalolae district of Kolaka. This study aims to determine the comparative income immigrants with indigenous peasant farmers in lowland rice farming, to determine the feasibility of paddy rice farming obtained Kesio farmer in the village, District Lalolae, in Kolaka. The research was conducted for approximately two months ie from January to March 2016. The results of this study Showed that the average production per hectare peasant settlers in the village Kesio, District Lalolae in Kolaka can increase of farmers' income every harvest season a production of 1,710 kg / ha with a selling price of Rp. 2,250 / Kg can generate revenue of Rp. 3,884,833, while the indigenous peasant production Reached 1,258 / ha at a price of Rp.2.250. then Rp.2.767.666 income, the value of R / C Ratio is at 2.7 indicate that paddy rice farming in the village Kesio, in Kolaka District Lalolae financially very viable farmers, Obtained t count = 2,003 and t the table was = 2.0336, meaning there is no real difference between revenues entrants indigenous peasant farmers in rice farming on Kesio Village, subdistrict Lalolae in Kolaka.